Religious Ethics in Cooperative Leadership: Fostering Trust Increases Member Involvement - Yayat Hidayat; Budi Santoso (CAKRAWALA : Management Science Journal, 2025)
This research is an applied research that aims to provide recommendations for religious ethics in Cooperatives, as an effort to foster trust in increase the involvement of cooperative members in the competitiveness of cooperatives. This study employs a qualitative approach, utilizing the Yamughni Cooperative as the research object. The researcher processed data on cooperative members to conduct an analysis of the leadership style in cooperative management. Currently, the cooperative is experiencing a decline in trust among members, which has led to a decrease in member involvement over the past few years. Based on the findings produced, the researcher concluded that the ethics of leadership in the management of cooperative x is still very low, as a result it often causes conflict with cooperative members, which has an impact on weakening member trust, as well as decreasing member participation, one of which is in the consumption of cooperative product shopping. This study is expected to be a positive suggestion for the ethics of cooperative leadership, so that it can increase member trust and increase member involvement in cooperatives